Clostridium butyricum attenuates LPS-induced myocardial injury in septic mice by modulating CD4 + CD25 + FOXP3 + Treg - Jinglin Zhao; Liuli Wu; Rupan Zhang; Mei Yuan; Junchao Huang; Xiongfei Jia; Xiaoqin Mao (Immunobiology)
Sepsis-induced myocardial injury has become a major threat to patient health and safety. Intestinal microbiota imbalance plays a crucial role in sepsis regulation. Using 16srRNA technology, we explored how intestinal colonization of Clostridium butyricum over 28 days impacted mice with LPS-induced sepsis. Significant changes were noted in the gut microbiota of the mice, highlighting that C. butyricum can positively influence the immune state in septic myocardial injury models. The bacterium's ability to prevent intestinal mucosal damage and alleviate the immunosuppressive state during the later stages of sepsis by regulating CD4 + CD25 + FOXP3 + Treg cells is particularly noteworthy. This suggests a therapeutic role for C. butyricum in sepsis management by protecting against myocardial injury and improving immune regulation.